2022
DOI: 10.1186/s12961-022-00933-z
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening research ethics governance and regulatory oversight in Central America and the Dominican Republic in response to the COVID-19 pandemic: a qualitative study

Abstract: Background Good governance and regulatory supervision are required to conduct research in an international public health emergency context and to ensure compliance with ethical standards. The “Strengthening research ethics governance and regulatory oversight in Central America and the Dominican Republic in response to the COVID-19 pandemic” study is a regional effort in which research ethics stakeholders participated in addressing research ethics governance and preparedness response challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…In this section, we present the results of studies that address the risks of framing policies/interventions in terms of so-called ‘best practices’ [ 39 , 40 ]. For example, initiatives such as prescribed social distancing or isolation are entirely unfeasible if applied in crowded living situations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we present the results of studies that address the risks of framing policies/interventions in terms of so-called ‘best practices’ [ 39 , 40 ]. For example, initiatives such as prescribed social distancing or isolation are entirely unfeasible if applied in crowded living situations.…”
Section: Resultsmentioning
confidence: 99%
“…Canario Guzman et al [ 39 ] called for a strengthening of research ethics and regulatory frameworks to facilitate strategic policy decisions that coordinate research efforts, aligning with priorities and ensuring accountability and transparency. The authors highlighted the importance of collaboration and knowledge sharing, both within and between national regulatory bodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these contributions focus exclusively on one ERC, usually associated with an academic or health care institution. The literature includes descriptions of ERC operations during the pandemic in Central America and the Dominican Republic [17], China [18], Ecuador [19], Egypt [20], Germany [21], India [2224], Iran [10], Ireland [25], Kenya [26], Kyrgyzstan [27], Latin America [28], the Netherlands [29], Pakistan [30], South Africa [31,32], Turkey [33], and the United States [3436]. Most of these studies reported results from surveys, interviews, focus groups, and documentary analysis, including review of research protocols, ERC meeting minutes, and existing SOPs.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these contributions focus exclusively on one ERC, usually associated with an academic or health care institution. The literature includes descriptions of ERC operations during the pandemic in Central America and the Dominican Republic [17], China [18],…”
Section: Discussionmentioning
confidence: 99%